PREGNANCY COMPLICATIONS IN WOMEN ADDICTED TO PAAN, GUTKA, CHALIA AND NASWAR. : J Peop Univ Med Health Sci. 2025:15(3), 64-70. http://doi.org/10.46536/jpumhs/2025/15.03.659 - Rahila Imtiaz1, Ome Kulsoom2, Sageera Anjum Munaver3, Urooj Malik4, Fasiha Mazhar5, Abida Shaikh6 , (Journal of Peoples University of Medical & Health Sciences Nawabshah. (JPUMHS), 2025)
BACKGROUND: The consumption of psychoactive substances during pregnancy remains a pressing global health concern. OBJECTIVE: This paper explores the impact of smokeless tobacco (SLT) products such as gutka, paan, naswar or chalia on pregnancy outcome in Karachi Pakistan. METHODS: We conducted a cross sectional observational study at Gynecology and Obstetrics Department of Abbasi Shaheed Hospital from June to December 2024. At the time of the study, pregnant women who had developed an addiction to SLT were included. Such patients should have consumed at least one gutka packet per day for a period of more than a year. The demography and clinical examination were assessed in a systematic way including assessment of anemia by complete blood count (CBC). Exclusion criteria included any woman who smoked tobacco or who was suffering from anemia unrelated to tobacco use. We carried out statistical analysis by using SPSS v23. 0 using chi-square tests, odd ratio and independent sample t-tests. RESULTS: SLT use during pregnancy was significantly associated with adverse maternal and fetal outcomes with major complications including anemia (p<0. 05), preterm delivery (p <0. 05), and congenital defects (p<0. 05). Prevalence of anemia did not appear to correlate with long-term SLT addiction. These data indicate the serious risks associated with SLT use during pregnancy. CONCLUSION: Smoking less tobacco during pregnancy poses serious health risks to women owing to abortion in spontaneous manner (stuck baby syndrome), still births, preterm delivery and low birth weight. This is to augment maternal and neonatal health issues prevalent in Karachi. This study highlights that urgent steps need to be taken in public health to mitigate this problem including efforts at awareness building, policy implementation and culturally sensitive cessation counseling.